2‐Monochloro‐1, 3‐propanediol (2‐MCPD) Dynamics in DGF Standard Methods and Quantification of 2‐MCPD. (11th May 2013) - Sato, Hirofumi; Kaze, Naoki; Yamamoto, Hiroshi; Watanabe, Yomi
Abstract: Pure 2‐monochloro‐1, 3‐propanediol (2‐MCPD) was successfully synthesized, identified, and first quantified by the Deutsche Gesellschaft für Fettwissenschaft (DGF) standard method C‐VI 18 (10), with a calculable detection sensitivity relative to 3‐monochloro‐1, 2‐propanediol (3‐MCPD) of 3.26‐fold, using a QP‐2010 GC/MS instrument. The detection sensitivities of other GC/MS instruments can be determined using the individual ion‐ratio of the fragment to the precursor of 3‐MCPD‐ d 5 as a reference. Quantification of 2‐MCPD is possible using conventional 3‐MCPD‐ d 5 esters as internal‐standards, without a calibration curve of pure 2‐MCPD. The dynamics of 2‐MCPD during DGF standard methods C‐VI 18 (10) were directly analyzed using NMR and indirectly using GC/MS. 2‐MCPD was partly converted to glycidol under basic conditions of the transesterification step, and the glycidol was reconverted to 2‐MCPD under acidic conditions of the extraction step. 2‐MCPD spiked in soybean oil was detected as 98 mol% 2‐MCPD and 2 mol% 3‐MCPD from the area ratio in GC/MS. In contrast, glycidyl stearate spiked in soybean oil was detected as 5.5–5.7 mol% 2‐MCPD and 94.3–94.5 mol% 3‐MCPD from the corrected area ratio in GC/MS.